Social capital and self-efficacy in the process of youth entry into the labour market: Evidence from a longitudinal study in Sweden. (February 2021) - Andersson, Anton B.
Highlights: Social capital and job finding self-efficacy are both positively related to achieving a stable labour market position for young job-searchers. The paper shows that social capital is related to job-finding self-efficacy measured as self-estimated job-finding probability. Results show that self-efficacy can explain only a little of the same variance as social capital in labour market outcomes. Social capital is negatively related to preferring the employment agency job search method and positively related to informal job search methods. Abstract: Social networks play an important role in the employer–worker match, and the social capital perspective has been used to understand how social networks contribute to labour market inequality. This paper investigates the effect of social capital on achieving a stable labour market position for young adults, examining how boosted job finding self-efficacy is a possible mediator. The paper also examines whether social capital and self-efficacy are related to the preferred job search method. The study utilises a Swedish survey of young adults that is linked to tax register data on earnings. Here, social capital is defined as an extensive network and measured with the position generator, asking about knowing contacts in various occupations. The paper analyses heterogeneous effects that depend on the respondents' initial status regarding employment and job search. The results show that social capital and job-finding self-efficacy are positively related to achieving stable employment for the initially not employed job searchers, but there is no effect for those initially employed and not searching for a new job. Furthermore, an analysis of job search methods reveals that social capital is positively related to preferring social networks and direct application and negatively related to searching through public employment services. The results also indicate that self-efficacy mediates only a little of the relationship between social capital and prospective employment, suggesting that job-finding self-efficacy likely only contributes slightly to how social capital affects labour market outcomes.